Framing Analysis of Policy News Analog Switch off (ASO) on Medcom.id and Okezone.com - Jalil, Abdul; Utari, Prahastiwi; Hastjarjo, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how Okezone.com and Medcom.id construct reality in their reporting on ASO policies using Robert N. Entman's framing analysis. A qualitative descriptive method was used, focusing on eight news articles (four from each outlet). This study analyzes how the media defines the implementation of ASO policies, diagnoses the causes, makes moral judgments, and proposes solutions. The findings point to a different framing strategy: Medcom.id, which is connected to Surya Paloh, the chairman of the NasDem Party, supports the policy through sources connected to the government. On the contrary, Hery Tanoesoedibjo's Okezone.com criticized the ASO policy so that it affected negative framing and the selection of critical sources. These different approaches describe how the construction of media reality is shaped by external factors and ideological influences. Understanding these dynamics encourages critical news consumption and awareness of media bias in shaping public opinion.